Socialization of Science Teaching Media as an Application of the Concept of Independent Learning - Srinatalia Silaen (EQUATOR SINAR AKADEMIA, 2022)
Abstract A. Background Independent Learning can be interpreted as learning that is regulated by students themselves. The meaning of this independence is that students can determine the goals, methods and assessments of their learning. From the teacher's point of view, independent learning means learning that involves students in setting goals, giving choices of ways, The concept of Independent Learning reflects on the process and learning outcomes. In essence, independent learning is learning that involves students in setting goals and providing choices for learning methods and collectively reflecting on the learning process and results. The independent learning policy is a step to transform education for the realization of Indonesia's Superior Human Resources (HR) who have the Pancasila Student Profile. There are 3 (three) ways to practice independent learning in the process of teaching and learning activities (KBM). Namely: building commitment to goals, building independent learning, fostering the habit of reflection Based on the problems that occurred in SD Negeri 091254 Batu Onom Pematangsiantar, the author thinks that there is a need for training on workshops and socialization of independent learning at SD Negeri 091254 Batu Onom Pematangsiantar. Hard skills must be accompanied by qualified soft skills. With increased socialization of teachers in schools can affect interest in learning and student learning outcomes. Therefore, it is necessary to hold training workshops and socialization to teachers at SD Negeri 091254 Batu Onom Pematangsiantar so that the soft skills of teachers can develop and improve. One of the trainings is training socialization of learning with the concept of independent learning as well as improving the soft skills of teachers at SD Negeri 091254 Batu Onom Pematangsiantar. B. Identification of Problems and Discussion Topics Based on the background of the problem above, the identification of the problem in this research is to develop science teaching media for teachers at SD Negeri 091254 Batu Onom Pematangsiantar through training workshops and socialization of learning the concept of independent learning. C. Purpose of Community Service Based on the formulation of the problem above, the purpose of this service is to develop the concept of independent learning at SD Negeri 091254 Batu Onom Pematangsiantar through workshop training and socialization of independent learning. D. Benefits 1. Theoretical Benefits: a. Increase knowledge and insight of science teaching media. b. Increase knowledge about the concept of independent learning 2. Practical Benefits, namely: a. Teacher: The results of this service are expected to help teachers in utilizing technology science teaching media at this time. b. Schools: The results of this study are expected to be a reference to be applied to every learning process in schools.